Dynamic Products Shaping Information to Engage and Persuade - Colombo, Sara (PoliMI SpringerBriefs, 2016)
This book explores how dynamic changes in products' sensory features can be used to convey information to the user in an effective and engaging way. The aim is to supply the reader with a clear understanding of an important emerging area of research and practice in product design, referred to as dynamic products, which is opening up new possibilities for the integration of product design with digital and smart technologies and offering an alternative to the use of digital interfaces. Dynamic products are artifacts displaying sensory characteristics - visual, tactile, auditory, or olfactory - that change in a proactive and reversible way over time, addressing one or more of the user's senses. The reader will learn why and how to communicate by means of such dynamic products. Their potential advantages and limitations are identified and design tools are proposed to support the design activity. It is hoped that the book will stimulate the design community to reflectupon the ever more compelling need to merge the virtual and the material in the information society by exploiting technological possibilities in order to create more meaningful and involving experiences.